Defining renal masses: comprehensive comparison of RENAL, PADUA, NePhRO, and C-index score - Kriegmair, Maximilian; Budjan, Johannes; Michel, Maurice Stephan; Wagener, Nina; Pfalzgraf, Daniel Philipp (Clinical genitourinary cancer, 2017)
Background: Nephrometry scores are designed for standardized reporting of renal tumors and predicting complications. Multiple scores are available, but there is a lack of systematic comparison. Patients and Methods: A total of 305 consecutive patients admitted for open partial nephrectomy to 2 urological hospitals were prospectively assessed. Five cases with conversion to radical nephrectomy were excluded from further analysis. RENAL, PADUA, C-index, and NePhRO scores were obtained from preoperative sectional imaging. Additionally, interobserver variance between 2 urologists and a radiologist was analyzed for 50 patients. Linear and ordered logistic regression was used to evaluate the association between scores and surgical parameters. Receiver operating characteristic analysis was employed to assess the predictive value for requirement of ischemia and opening of the collecting system. Results: High interobserver agreement was observed for RENAL (0.92 and 0.80), PADUA (0.81 and 0.85), NePhRO (0.94 and 0.82), and the C-index (0.98 and 0.95). All scores showed a significant association with opening of the collecting system (P < .016), requirement of on-clamp excision (P < .001), and ischemia time (P < .001). Logistic regression identified RENAL, PADUA, and NePhRO score to be an independent predictor for severe complications (P = .016, P = .011, and P = .005). No correlation was found for the C-index (ß = 0.98; P = .779). Predictive effectiveness for opening of the collecting system and for on-clamp excision showed comparable area under the curve values for the 4 scores. Conclusion: All scoring systems represent objective and reproducible measurement tools for renal tumor complexity, that correlate well with surgical outcome. RENAL, PADUA, and NePhRO score are comparable and seem to be superior to the more complex C-index system.